The reception of displaced persons from Ukraine in Portugal - Angelis, Gabriele De (2023)
Since the beginning of the invasion of Ukraine by the armed forces of the Russian Federation on 24 February 2022, Portugal was one of the first countries to activate the temporary protection regime for displaced persons from Ukraine, successively amended on the basis of the Temporary Protection Directive, triggered by the Council of European Union on 4 March 2022. Considering the massive and sudden influx of displaced persons from Ukraine, this policy brief aims to analyse the functioning of the national reception system and its adjustment to the current situation of extraordinary access to the system. What are the major challenges encountered? How have the institutions in charge of managing the international protection system reacted? What innovations can be identified in relation to the management of previous flows? What about the standard procedure for reception in the context of international protection? What can we learn from the current management of flows? What improvements can be suggested for the present and for the future?